2017
DOI: 10.21767/2171-6625.1000215
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Positive Interaction between Exercise and Mental Health

Abstract: Brain plasticity is a complex mechanism which depends on a variety of environmental and external parameters, including physical activity. Thus, cerebral plasticity may be improved with increased physical activity as a complement to therapy or cognitive training in the case of mental health problems. Many correlations were already reported in the current literature between practice of exercise, and improvement of cognitive function, mental health and state of participants with neurodegenerative diseases. The cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Physical activity reduces the risk of multiple chronic diseases, including diabetes, osteoarthritis, and hypertension, and it improves the general health, cognitive function, and quality of life ( Committee, 2018 ). Physical activity not only improves physical health, but also mental well-being by promoting self-esteem, alleviating symptoms of depression, anxiety, stress, and other mental and mood disorders ( Sosso and Raouafi, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Physical activity reduces the risk of multiple chronic diseases, including diabetes, osteoarthritis, and hypertension, and it improves the general health, cognitive function, and quality of life ( Committee, 2018 ). Physical activity not only improves physical health, but also mental well-being by promoting self-esteem, alleviating symptoms of depression, anxiety, stress, and other mental and mood disorders ( Sosso and Raouafi, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have also demonstrated a positive effect of regular exercise to prevent the development of atherosclerosis (Khosravani et al, 2016), as well as improve immune part of healthy lifestyle. Regular exercise contributes to physical and physiological health (Ohuruogu, 2016), as well as mental well-being (Sosso & Raouafi, 2017). Studies found that regular exercise improves immune system against free radical that can cause oxidative damage.…”
Section: Introductionmentioning
confidence: 99%
“…An important part of this modern age is the possibility to complete almost everything online or by phone. Even if this evolution makes our lives easier, evidence suggests that cell phones have a negative impact on our physical health, our socialization and our brains (Wei et al, 2012; Arora et al, 2013a; Etindele Sosso and Raouafi, 2016; 2017; Etindele Sosso, 2018). Many studies reported associations between lack of physical activity and obesity (Arora et al, 2013a; Arora et al, 2013b), between poor and moderate physical activity and cardiovascular diseases (Nicholson et al, 2012; Etindele Sosso and Raouafi, 2016), or development of cognitive impairment with an excessive use of technology (Shams et al, 2015).…”
Section: Introductionmentioning
confidence: 99%